Pointer dynamics as cognitive biometrics - Cunha, Liliana (2019)
Biometric authentication technologies aim to increase the precision of security systems and have given proof of their effectiveness. Cognitive biometrics, in particular, has shown the potential of raising security levels, although lacking somewhat in terms of precision and adequate research. Therefore, this study analyses the viability of the usage of the Pointer Dynamics biometric technique as cognitive biometrics, under certain conditions. To this end, an algorithm was developed, whose identity validation criterion is the execution of the individual pattern in the manner of interaction with the mouse, when selecting the grids of the graphic secret. Authentication and fraudulent authentication tests were conducted with two types of images, one with a supposed emotional meaning for the user, and one without. This was done so as to allow the comparison of results brought forth by the application of the technique with and without cognitive stimulus. Although results do not allow definite conclusions to be drawn, the fact is that the False Acceptance Rate of both the cognitive tests and graphs present marked relative variations, for thresholds between 4 and 7, which indicate that it is likely that the cognitive stimulus has increased the resistance to attempts of fraudulent authentication.